Parametric study of a box type solar cooker : computer simulation [compact disc] - 241181 Nazman Che Iberahim (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006